Pendampingan Masyarakat dalam Membangun Lingkungan Bersih di Era Pandemi Covid-19 - Rusni Podungge; Irmawaty Umar (Univeristas Negeri Gorontalo, 2022)
The KKN-Thematics Activity Program to Build a Village aims to direct the community in building a social environment during the covid-19 pandemic. Many people know about social distanting, physical distancing, always wear a mask when traveling outside the house, always wash their hands after activities outside the house, and some other health slogans, but do not realize that not only ourselves are guarded, but the environment as well. Because people get used to or teach people to live clean and healthy lives are still difficult. The method used in the KKN-Thematics Program to Build Villages is assistance to community elements in building a clean environment during the Covid-19 pandemic. People will also be taught knowledge, understanding of the environment and clean society, in an effort to minimize the occurrence of pandemics in the villages of West Pentadu and Hungayonaa. Evaluation is carried out to obtain information not only as learning materials for related communities but also related to the implementation of clean lifestyle through the movement of community elements and students of KKN Thematic Village Building.